1997
DOI: 10.1177/082585979701300403
|View full text |Cite
|
Sign up to set email alerts
|

Is there a Relationship between Psychological Well-Being and Patient-Carers Consensus? A Clinical Pilot Study

Abstract: Does communication with terminal cancer patients about their disease influence their psychological well-being? The degree of patient-carer consensus about the disease was compared to psychological well-being related to acceptance of the disease, emotional state, and hope. These were evaluated and scored from 6 (good) to 0 (poor) through a semi-structured interview of 10 open-ended questions. Nineteen palliative care patients were studied, 18 of whom were suffering from advanced cancer. Overall, 57 interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Greisinger et al (1997) found it was important for such patients to have a sense of hope, know that life has meaning and purpose, and believe that life has been productive. Similarly, several other researchers found that living with meaning and hope was a significant factor that assisted individuals to adjust their cancer illness (Taylor 1993), to reduce psychological distress and enhance their PSW and QOL (Lewis 1989, Bishara et al 1997, Axelsson & Sjoden 1998, Yang & Yin 1999, McMillan & Weitzner 2000, Morita et al 2000, and to develop a sense of a good death (Chao 1997).…”
Section: Living With Meaning and Hopementioning
confidence: 93%
See 2 more Smart Citations
“…Greisinger et al (1997) found it was important for such patients to have a sense of hope, know that life has meaning and purpose, and believe that life has been productive. Similarly, several other researchers found that living with meaning and hope was a significant factor that assisted individuals to adjust their cancer illness (Taylor 1993), to reduce psychological distress and enhance their PSW and QOL (Lewis 1989, Bishara et al 1997, Axelsson & Sjoden 1998, Yang & Yin 1999, McMillan & Weitzner 2000, Morita et al 2000, and to develop a sense of a good death (Chao 1997).…”
Section: Living With Meaning and Hopementioning
confidence: 93%
“…They found that telling terminally ill cancer patients the truth about their diagnosis, pathology, and prognosis was related to feeling more fulfilled at the end of life. Bishara et al. (1997), using a triangulation approach, found a positive relationship between communication and psychological well‐being, and concluded that truthful communication does improve a patient's psychological well‐being.…”
Section: Self‐awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, prognostic information that is tailored to a patient’s preferences has potential to improve their psychological wellbeing 1,33. Tailored prognostic information has been found to result in higher satisfaction with care, lower anxiety and depression scores, and even improved cognitive function 3436.…”
Section: Current Communication Practicesmentioning
confidence: 99%
“…For example, survey evidence suggests that medical professionals may underestimate the distress caused by side‐effects of treatment to patients with cancer in many cases (Leonard et al 1996). Conversely, consultations characterized by more complete and accurate communication are more likely to deliver greater patient satisfaction and improved psychological well‐being (Butow et al 1995; Bishara et al 1997). Many medical professionals involved in the provision of colorectal cancer care support this view, as indicated by a survey carried out in Europe and the USA, which revealed significant support for improved information provision and education of patients (International Working Group in Colorectal Cancer.…”
Section: Introductionmentioning
confidence: 99%